Solving Gain Saturation Issue with GC-EDFA - T, Subramaniam; S.W, Harun; P, Poopalan; H, Ahmad (Malaysian Journal of Science, 2003)
This paper discusses the gain-clamped erbium-doped fibre amplifier system that is designed to solve the gain saturation issue experienced by the erbium-doped fibre amplifier system in a wavelength division multiplexer environment. The EDFA_Design software is used to show the critical gain saturation issue that is experienced by the erbium-doped fibre amplifier in a simple wavelength division multiplexer system. This software was then used to simulate the gain-clamped erbium-doped fibre amplifier system characteristics and finally to simulate the performance of the gain-clamped erbium-doped fibre amplifier system in a simple wavelength division multiplexer system in order to show that the use of this device solves the gain saturation issue.